DAMPAK ONLINE MARKETING MELALUI FACEBOOK TERHADAP PERILAKU KONSUMTIF MASYARAKAT - Triyaningsih, SL . (Universitas Slamet Riyadi, 2011)
ABSTRACT In the era of new marketing, facebook can be one of the media played a major role. With the ease of socializing on facebook, sometimes a person is difficult because sometimes decisions are influenced by what is filtered from the results of observing the behavior of others in a community. When someone wants to buy something, it could be asked for consideration to the community, so that promotional products can be done in the community. Promotion in facebook do for friends who are already in the previous add. Promotion was held by a change in status facebook owned. Can also pass notes (notes) in facebook, then do the delivery to the community of friends on facebook so that the information written in the notes may spread to the community. Promotion can be obtained free of charge, so for a new product that does not cost a lot. Although the possibility of the results obtained is also less. Facebook has proved to be the most effective media to maximize the sale marketing. Facebook is not just a social networking site in the community, but became one of the media to obtain information about the marketing of goods, such as fashion products. Fashion is an important part of people's lifestyles especially among students. Because fashion is the objects or attributes are used for someone to identify themselves as clothing, bags, shoes and so on. Keywords: Online Marketing, Consumptive Behavior.